O Transtorno de Déficit de Atenção e Hiperatividade (TDAH) na perspectiva de psicólogos que atuam na clínica e na escola - Santos, Roseli de Melo Germano Marques dos (2012)
Most behaviors considered inadequate in children have been diagnosed as ADHD (Attention Deficit Hyperactivity Disorder), with the indication of the use of medication in order to control it. The dominant conception about ADHD reveals a comprehension that ignores the social factors involved in its diagnosis, transforming it into one of the most adopted medical descriptions used to vent the mechanism of turning the difficulties emerged in childhood into psychopathologies, especially those that are related to school. Regarding this, the current inquiry focused on studying the disorder throughout a critical outlook, concerned about avoiding the Organicist conceptions built on the theme, which interpret hyperactive and distracted behaviors presented by children as consequences of neurological dysfunctions. In order to do so the following objectives have been defined: deepening the knowledge of the concepts of the Cultural-Historic Theory, focusing on the aspects that involve the development of the higher psychological functions, particularly regarding the development of attention; and investigating the comprehension adopted by clinical psychologists and scholars about the ADHD, in an attempt to discover if they operate according to the biological/psychopathological perspective, that is, treating the conflicts related to social issues as a biological or psychological phenomena, of if they function understanding these conflicts as symptoms of those issues. The data was treated within two different groups, one of them counting with six psychologists that work inside the public educational system in three cities located in Paraná state, and the other one with six psychologists that work in private clinics, with the objective of investigating if the biological/psychopathological ADHD perspective is the dominant paradigm in both educational and clinical environments. The theoretical framework adopted in the scientific foundation of the current work and the analysis of the collected data was mainly guided by the Cultural-Historic Psychology paradigm, which is based upon Karl Marx's Historical and Dialectic Materialism, a theoretical view that